2022
DOI: 10.1063/5.0125432
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion theory of molecular liquids in the energy representation and application to solvation dynamics

Abstract: The generalized Langevin equation (GLE) formalism is a useful theoretical fundament for analyzing dynamical phenomena rigorously. Despite the systematic formulation of dynamics theories with practical approximations, however, the applicability of GLE-based methods is still limited to simple polyatomic liquids due to the approximated treatment of molecular orientations involved in the static molecular liquid theory. Here, we propose an exact framework of dynamics based on the GLE formalism incorporating the ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 82 publications
1
5
0
Order By: Relevance
“…In addition, S ( t ) in water shows the damped oscillation at Dt < 0.2 Å 2 . In our previous study, 50 a similar oscillation is observed for the solvation dynamics of benzonitrile in water due to the rotational motion of the water molecules hydrogen bonded with benzonitrile. The rotational motion of the water molecules would also bring the oscillation observed in the present water system.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…In addition, S ( t ) in water shows the damped oscillation at Dt < 0.2 Å 2 . In our previous study, 50 a similar oscillation is observed for the solvation dynamics of benzonitrile in water due to the rotational motion of the water molecules hydrogen bonded with benzonitrile. The rotational motion of the water molecules would also bring the oscillation observed in the present water system.…”
Section: Resultssupporting
confidence: 76%
“…The formulation for multi-component solvents is available in ref. 50. Furthermore, we assume that the solute molecule is fixed in space.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations